Intra- and intersession reliability and agreement of the Unilateral Seated Shot-Put Test outcome measures in healthy male athletes - Matthieu Degot; Yoann Blache; Grégory Vigne; Gabriel Franger; Lionel Neyton; Isabelle Rogowski (BMC, 2021)
Abstract Background The Unilateral Seated Shot-Put Test (USSPT) consists of pushing an overweight ball as far as possible to assess upper extremity power unilaterally and bilateral symmetry. Literature however reports various body positions and upper limb pushing patterns to perform USSPT, demanding to provide additional guideline to achieve overweight ball push. This study therefore aimed at assessing the reliability and agreement of USSPT outcome measures when pushing an overweight ball in a horizontal direction. Methods Twenty-seven healthy male athletes performed two sessions, one week apart, of three unilateral pushes per upper limb using a 3-kg medicine ball, for which the distances were measured. The intraclass correlation coefficient (ICC), standard error of measurement (SEM), minimum detectable change at a 95 % confidence level (MDC95 %) and coefficient of variation (CV) were assessed for the pushing distances based on one, two or three trials per side to produce two outcome measures: the pushing distance per limb and USSPT Limb Symmetry Index (LSI) when dividing pushing distance of the dominant side by that of the non-dominant side. Results The most reliable pushing distance per limb was obtained when averaging three pushing distances, normalized by body mass with the exponent 0.35. The mean USSPT LSI was 1.09 ± 0.10 for the first session and 1.08 ± 0.10 for the second session, highlighting good reliability and agreement (ICC = 0.82; SEM = 0.045; MDC95 % = 0.124; CV = 5.02 %). Conclusions When the overweight ball is pushed in a horizontal direction, averaging the distances of three trials for both the dominant and non-dominant limbs is advised to provide the most reliable USSPT distance per limb and USSPT LSI.